Uncovering the Self: Psychological Growth in Loulie al-Nazari’s Journey in The Stardust Thief - Tito Mahesa Wijaya; Ambar Andayani (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This research investigates the psychological transformation of Loulie al-Nazari, protagonist of Chelsea Abdullah’s The Stardust Thief, by combining Christopher Vogler’s twelve-stage adaptation of Joseph Campbell’s monomyth with Carl Jung’s theory of archetypes. Three aims guide the study: identifying how Vogler’s twelve stages manifest in Loulie’s narrative arc, determining which internal and external factors drive her psychological development, and evaluating the resulting shift in her identity and self-perception. A qualitative descriptive design, supported by close reading and content analysis of the novel as primary data, is used to reach these aims. Results indicate that Loulie’s arc realizes all twelve of Vogler’s stages, opening with a forced call to adventure and advancing through mounting trials before reaching a decisive reckoning with her hidden past inside the ruins of the Queen of Dunes. Jung’s archetypes account for the internal dimension of this development: the Shadow surfaces as the grief she buries after her tribe’s destruction, the Persona takes shape as the Midnight Merchant guise she uses for self-protection, and the Animus emerges in the resilience and nerve she calls upon across the quest. Externally, the surrounding cast enacts Vogler’s archetypal roles, Qadir as Mentor, Omar as Shadow, Mazen as Ally, and Aisha as Shapeshifter. As the narrative closes, Loulie edges toward individuation, reclaiming a name and history she once suppressed and arriving at a more unified sense of self. The research concludes that Abdullah’s novel illustrates the continued cross-cultural relevance of the Campbell–Vogler model.